2016
DOI: 10.1186/s12912-016-0186-y
|View full text |Cite
|
Sign up to set email alerts
|

European Academy of Nursing Science 2016 Summer Conference

Abstract: VenUS IV (Venous leg Ulcer Study IV) -compression hosiery compared with compression bandaging in the treatment of venous leg ulcers: a randomised controlled trial, mixed-treatment comparison and decisionanalytic model. Health Technol Assess 2014;18(57). 4. Nixon J, Cranny G, Iglesias C, Nelson EA, Hawkins K, Phillips A et al. Randomised, controlled trial of alternating pressure mattresses compared with alternating pressure overlays for the prevention of pressure ulcers: PRESSURE (pressure relieving support sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…As members of the healthcare team, nurses play a vital role in improving patient safety, originating from their attitudes, knowledge, and skill in patient safety [15,24]. Also, the WHO emphasizes teaching patient safety to medical and nursing students, and the ministries of health focus on patient safety programs [25].…”
Section: Introductionmentioning
confidence: 99%
“…As members of the healthcare team, nurses play a vital role in improving patient safety, originating from their attitudes, knowledge, and skill in patient safety [15,24]. Also, the WHO emphasizes teaching patient safety to medical and nursing students, and the ministries of health focus on patient safety programs [25].…”
Section: Introductionmentioning
confidence: 99%
“…They also indicated that nurses must ensure patient safety is confirmed even with physical restraint. 15 In this study, the students have also mentioned different physical restraints they have encountered during their practicum in the ward. Lai et al 16 found that the most common form of physical restraint is bedrails (16.9%), followed by jacket restraint.…”
Section: Discussionmentioning
confidence: 99%
“…In their dual roles as care providers and ‘guardians of patient safety’ [ 7 ], and per their professional standards and codes of ethics, nurses are obliged to keep accurate records. Charting is a key component of ethical and professional nursing practice and patient record keeping must be objective, accurate, and timely [ 8 ].…”
Section: Introductionmentioning
confidence: 99%